KESALEHAN SOSIAL MASYARAKAT KETURUNAN ARAB DI INDONESIA - Medina Chodijah (Syifa al-Qulub, 2020)
This research is motivated by the diversity of ethnic groups in Indonesia; one of them is the Arab-Indonesian tribe. Arab descendant communities have existed and been part of the Indonesian nation since the 13th century. They have assimilated and experienced acculturation in various aspects of life with indigenous Indonesian people. Various studies have shown that although there has been a mixture of various aspects of culture adopted by people of Arab descent; but they still maintain Islamic values including relations with other human beings which are actually the values of their family's ancestors. This study aims to obtain valid and up-to-date data on the extent of the social piety of people of Arab descent in daily life. This research is a descriptive study with a quantitative approach. The sample used in this study came from populations of people of Arab descent in a number of major cities in Indonesia. The instrument used in this study was a modification questionnaire from COSE compiled by Prof. Dr. Günter Bierbrauer, Ph.D and Individualism and Collectivism Scale compiled by Triandis, H. C. & Gelfland, M. Data obtained are then presented in tabular, graphical form and processed using statistical techniques. The results showed that the community of Arab descent in Indonesia is a society that adheres to the value of collectivism when it comes to close family, power distance between generations is very low, and a polychromatic time value system. They also have high self-confidence, are independent and act in accordance with the demands of social norms.